The Neosartorya (Aspergillus) fischeri antifungal protein NFAP2 has low potential to trigger resistance development in Candida albicans in vitro - Gábor Bende; Nóra Zsindely; Krisztián Laczi; Zsolt Kristóffy; Csaba Papp; Attila Farkas; Liliána Tóth; Szabolcs Sáringer; László Bodai; Gábor Rákhely; Florentine Marx; László Galgóczy (Microbiology Spectrum)
ABSTRACT Due to the increase in the number of drug-resistant Candida albicans strains, new antifungal compounds with limited potential for the development of resistance are urgently needed. NFAP2, an antifungal protein (AFP) secreted by Neosartorya (Aspergillus) fischeri, is a promising candidate. We investigated the ability of C. albicans to develop resistance to NFAP2 in a microevolution experiment compared with generic fluconazole (FLC). C. albicans adapted to only 1× minimum inhibitory concentration (MIC) of NFAP2, which can be considered tolerance rather than resistance, compared with 32× MIC of FLC. Genome analysis revealed non-silent mutations in only two genes in NFAP2-tolerant strains and in several genes in FLC-resistant strains. Tolerance development to NFAP2 did not influence cell morphology. The susceptibility of NFAP2-tolerant strains did not change to FLC, amphotericin B, micafungin, and terbinafine. These strains did not show altered susceptibility to AFPs from Penicillium chrysogenum, except one which had less susceptibility to Penicillium chrysogenum antifungal protein B. FLC-resistant strains had decreased susceptibility to terbinafine and NFAP2, but not to other drugs and AFPs from P. chrysogenum. NFAP2-tolerant and FLC-resistant strains showed decreased and increased NFAP2 binding and uptake, respectively. The development of tolerance to NFAP2 decreased tolerance to cell wall, heat, and UV stresses. The development of FLC resistance increased tolerance to cell wall stress and decreased tolerance to heat and UV stresses. Tolerance to NFAP2 did not have significant metabolic fitness cost and could not increase virulence, compared with resistance to FLC.IMPORTANCEDue to the increasing number of (multi)drug-resistant strains, only a few effective antifungal drugs are available to treat infections caused by opportunistic Candida species. Therefore, the incidence of hard-to-treat candidiasis has increased dramatically in the past decade, and the demand to identify antifungal compounds with minimal potential to trigger resistance is substantial. The features of NFAP2 make it a promising candidate for the topical treatment of Candida infection. Data on the development of resistance to antifungal proteins in Candida albicans are lacking. In this study, we provide evidence that NFAP2 has a low potential to trigger resistance in C. albicans in vitro, and the developed tolerance to NFAP2 is not associated with severe phenotypic changes compared with development of resistance to generic fluconazole. These results suggest the slow emergence of NFAP2-resistant Candida strains, and NFAP2 can reliably be used long-term in the clinic.